Early sexual debut and pregnancy termination: uncovering the link among sexually active young women in 23 sub-Saharan African countries - Obasanjo Afolabi Bolarinwa (BMC, 2024)
Abstract Background Unplanned pregnancy could be a socio-economic burden for many young women in sub-Saharan Africa (SSA) which often leads to pregnancy termination. The role of age at sexual debut in pregnancy termination in countries with lower income remains unknown. Hence, this study examines the association between age at sexual debut and pregnancy termination among sexually active young women between the ages of 15 -24 in 23 SSA countries. Methods Cross-sectional secondary datasets from the most recent Demographic and Health Survey conducted in 23 countries in SSA conducted between 2010 and 2018 among 34,343 sexually active young women were analysed using bivariate and multivariable logistic regression to examine the association between age at sexual debut and pregnancy termination with statistical significance of p < 0.05. Results The pooled prevalence of pregnancy termination among sexually active young women in SSA was 11.00%. Higher odds of pregnancy termination were found among those who had early sexual debut (below 16 years) [(aOR = 1.34, 95% CI = (1.22-1.48)] compared to those who had late sexual debut. Furthermore, those who were exposed to mass media [(aOR = 1.29, 95% CI = (1.16-1.43)] were more likely to report pregnancy termination compared to those who were not exposed. On the other hand, those residing in rural areas and those within the richest wealth index were associated with lower odds of pregnancy termination. Conclusion The study concluded that early sexual debut of sexually active young women in SSA was significantly associated with pregnancy termination. Mass media exposure was found to be a risk factor for pregnancy termination whilst residing in rural areas, and those within the richest wealth index were protective factors. Interventions should be designed to target young women with early sexual debut to provide comprehensive sexual and reproductive health education to enable them to make informed decisions on pregnancy termination.